Implementasi Fungsi Manajemen dalam Kegiatan Dakwah Menggunakan Sosial Media di Masjid Al-Musannif Medan - Tengku Sri Mutiara; Winda Kustiawan (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to determine the implementation of management functions in da'wah activities at the Al-Musannif mosque in Medan and to see how the implementation of da'wah activities uses social media at the Al-Musannif mosque in Medan. This study used qualitative research methods. The type of data used in this research analysis is qualitative data and the data source used for this research is library research. Using data collection techniques in the form of observation, interviews and documentation. There are data analysis techniques, namely data reduction, data presentation and drawing conclusions. The research results show that the implementation of management functions in da'wah activities at the Al-Musannif Mosque in Medan consists of four elements, namely planning, organizing, implementing and supervising. The implementation of da'wah activities using social media at the Al-Musannif mosque in Medan was carried out very well and regularly. Starting from Facebook called @Masjid Al-Musannif, Instagram @Yayasan Haji Anif and YouTube @Yayasan Haji Anif. All activities that will be carried out will be shared on social media by distributing flyers on Facebook and Instagram, da'wah or recitation events will be uploaded on the YouTube account @Yayasan Haji Anif.